2013
DOI: 10.5217/ir.2013.11.1.52
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Ischemic Colitis Presenting as Bloody Diarrhea after Glycerin Enema

Abstract: Enema has frequently been used for diagnostic or therapeutic purpose. However, cases of colitis from physical, chemical, and thermal injury due to enema have been reported. In severe cases, life threatening complications (perforation, rupture, peritonitis, etc.) may occasionally occur. Reports of ischemic colitis after enema is rare and there have been only 1 case of ischemic colitis after normal saline enema reported in South Korea. Sigmoidoscopy on a 58 year old female, presenting with sudden abdominal pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Park et al [ 14 ] reported a case of IC that occurred within 2 h of normal saline enema for preoperative bowel cleansing. Most recently, Yoon et al [ 15 ] reported a case of IC that presented abdominal pain and hematochezia within 30 min of enema administration. Our data suggest that it may be necessary to observe patients receiving glycerin enema in the early period after administration (at least 4 to 8 h), considering timing of IC and high surgical resection rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al [ 14 ] reported a case of IC that occurred within 2 h of normal saline enema for preoperative bowel cleansing. Most recently, Yoon et al [ 15 ] reported a case of IC that presented abdominal pain and hematochezia within 30 min of enema administration. Our data suggest that it may be necessary to observe patients receiving glycerin enema in the early period after administration (at least 4 to 8 h), considering timing of IC and high surgical resection rates.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were as follows: (1) Patients with unspecific vascular hypoperfusion or its similar condition ( e.g ., cardiac failure, septic shock, hemodynamic shock, hemodialysis, and aortic surgery), colonic obstruction (volvulus, adhesion, stricture, hernia, colon cancer, or metastasis), vascular occlusion (based on the findings of follow-up CTs performed after enema), and infectious or inflammatory bowel disease ( e.g. , inflammatory bowel disease, radiation colitis, and infectious colitis); and (2) Time interval from enema administration to IC occurrence of > 24 h based on the prior case reports[ 13 - 15 ]. Among 17087 adult patients receiving enema in the ED, 542 patients were excluded due to infectious or inflammatory bowel disease ( n = 123), colonic malignancy ( n = 283), and mechanical ileus ( n = 136).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation